HUBUNGAN PENGGUNAAN APLIKASI RAPORT DIGITAL DENGAN KINERJA GURU (Penelitian di Madrasah Tsanawiyah Negeri Se-Kabupaten Sumedang) - Tatang Ibrahim; Moh Sulhan; Rida Nurfauziyyah (Jurnal Inovatif Manajemen Pendidikan Islam, 2022)
The digital report card application is a form of implementation of government policies where technology has now entered the realm of education. So that the digital report card application increases productivity and effectiveness, especially teachers. This study aims to describe: (1) the use of the digital report card application in Public Madrasah Tsanawiyah throughout Sumedang Regency (2) the performance of teachers in Public Madrasah Tsanawiyah throughout Sumedang Regency and (3) the relationship between the use of digital report cards application with the performance of Madrasah Tsanawiyah Negeri teachers. throughout Sumedang Regency. This study uses a quantitative research method by distributing questionnaires as many as 31 teacher samples with a population of 152 using a Likert scale model distributed by using the Goggle Form. Based on data analysis and research results show that: (1) the use of the digital report card application in Madrasah Tsanawiyah Negeri in Sumedang Regency is a high qualification from the results of the research on 31 respondents (2) the performance of teachers at Madrasah Tsanawiyah throughout Sumedang Regency is very qualified. from the results of the research to 31 respondents and (3) there is a strong and significant relationship between the use of the digital report card application and teacher performance by obtaining a correlation coefficient value of 0.644. This means that the higher the use of the digital report card application, the higher the performance of State Madrasah Tsanawiyah teachers in Sumedang Regency. Thus it is recommended that teachers increase the use of digital report cards to improve teacher performance. Key Words: Usage, Digital Report Card Application, Teacher Performance